Corneal Epithelial Remodeling and Its Effect on Corneal Asphericity after Transepithelial Photorefractive Keratectomy for Myopia. (8th September 2016) - Hou, Jie; Wang, Yan; Lei, Yulin; Zheng, Xiuyun; Zhang, Ying
Abstract : Purpose. To evaluate the changes in epithelial thickness profile following transepithelial photorefractive keratectomy (T-PRK) for myopia and to investigate the effect of epithelial remodeling on corneal asphericity. Methods. Forty-four patients (44 right eyes) who underwent T-PRK were retrospectively evaluated. Epithelial thickness was measured using spectral-domain optical coherence tomography at different corneal zones (central, 2 mm; paracentral, 2–5 mm; and mid-peripheral, 5-6 mm) preoperatively and at 1 week and 1, 3, and 6 months postoperatively. The correlation between the changes in corneal epithelial thickness (ΔCET) and postoperativeQ -value changes (ΔQ) was analyzed 6 months postoperatively. Results. Epithelial thickness at 6 months showed a negative meniscus-like lenticular pattern with less central thickening, which increased progressively toward the mid-periphery (3.69 ± 4.2, 5.19 ± 3.8, and6.23 ± 3.9 μ m at the center, paracenter, and mid-periphery, resp., P < 0.01 ). A significant positive relationship was observed between epithelial thickening and ΔQ 6 months postoperatively (r = 0.438, 0.580, and 0.504, resp., P < 0.01 ). Conclusions. Significant epithelial thickening was observed after T-PRK and showed a lenticular change with more thickening mid-peripherally, resulting in increased oblateness postoperatively. Epithelial remodeling may modify the epithelial thickness profile after surface ablation refractive surgery for myopia.